The Extent and Implications of Poly-drug Use in Ireland - Hogan-Murphy, Diana (Trinity Student Medical Journal, 2006)
The phenomenon of poly-drug use is prevalent in Ireland. Statistics from the National Drug Treatment Reporting System show that this behaviour is increasing, from 5590 cases treated in 1998 to 7845 cases treated in 2002. The most frequent combinations include: heroin and cannabis when two drugs are implicated; heroin, methadone and benzodiazepines when three drugs are involved; and heroin, methadone, benzodiazepines and cannabis when four drugs are consumed. Opiate-related deaths account for the largest proportion of fatalities amongst drug users, with most of the deaths attributable to consumption of heroin in combination with benzodiazepines, alcohol, methadone and cocaine. There is a significant problem of driving under the influence of drugs in Ireland. Results of a nationwide survey carried out by the Medical Bureau of Road Safety demonstrates that there is a strong trend of increasing positive drug tests with decreasing levels of alcohol, 68% of drivers with blood alcohol concentrations below the legal limit were positive for one or more drugs. There is a need for treatment services dealing with poly-drug use as services in Ireland remain focussed on individual drugs of abuse.